DOKUMENTASI ETNOBOTANI-LINGUISTIK TUMBUHAN SAGU: LAPORAN AWAL DARI ETNIS MARORI DI TAMAN NASIONAL WASUR MERAUKE - Hisa, La; Mahuze, Agustinus; Arka, I Wayan (Masyarakat Linguistik Indonesia, 2017)
This paper discusses the ethnobotanical-linguistic documentation of sago (sago Metroxylon Rottb.) in Marori. Sago is a plant of high socio-cultural and economic values for the Papuan people in general and for the Marori ethnic group in particular. Socio-culturally, sago plays a central role in everyday life: it is used in a variety of important rituals, from birth to funeral ceremonies, which involve certain social obligation and responsibility. It is the identity of the Mahuze clan. Traditionally sago has a high economic value too, as staple food. However, there has been a widespread process of acculturation and change resulting in a shift, among other things, in the consumption patterns of staple food, from sago to rice. In addition, the Marori language is highly endangered; the local indigenous knowledge related to sago (and also other plants) is also increasingly endangered. This is mainly due to external socio-historical-cultural factors that have affected and shaped the current ecology in Merauke and in modern Indonesia. The role of language is central in the intergenerational transmission of indigenous knowledge. Collaborative efforts of all stakeholders are therefore urgently needed to do language and cultural documentation, as part of the conservation and preservation of language and culture of this ethnic group. The discussion on the entholinguistics of sago in this paper addresses two related aspects, namely documentation aspects and ethnobotanical-linguistic aspects. The discussion on the folk taxonomy and lexical items in relation to sago plants and sago processing highlights rich vocabulary related to socio-cultural knowledge of sago. The paper also discusses the socio-cultural and economic significance of sago, outlining a sago-trading taboo posing a delicate problem in maximizing the economic potential of sago, and the efforts so far done to address the issues by relevant stakeholders.